Peningkatan Kelembagaan Kelompok Tani Peserta Program Integrate Participatory Development and Management of Irrigation Program (IPDMIP) di Kecamatan Lengayang Kabupaten Pesisir Selatan - Ilham Martadona; Angelia Leovita; Dian Fauzi; Yulia Rahmawati Z (Universitas Maritim AMNI Semarang, 2024)
Integrated Participatory Developmenet and Management of Irrigation Program (IPDMIP) is one of the government programs contained in Indonesia's 2005-2025 RPJPN to support national food security. Strengthening farmer groups is one thing that supports the successful implementation of the IPDMIP program. The problems that occur include; Farmer groups are not used as a forum for achieving collective goals but rather for achieving individual goals. Farmer group development programs are not carried out consistently, and there is still a lack of counseling and assistance for farmer groups. The solution offered to overcome this problem is direct education to management and members of farmer groups. The direct counseling method used is a combination of lecture and discussion. The results of the outreach carried out increased the knowledge of farmer group members. Strengthening farmer institutions is very necessary in the context of protecting and empowering farmers. Farmers can develop institutions from, by and for farmers to strengthen and fight for the interests of farmers themselves in accordance with a combination of culture, norms, values and local wisdom of farmers.